Defects in epoxy‐coated reinforcement and their impact on the service life of a concrete structure. (September 2015) - Keßler, Sylvia; Angst, Ueli; Zintel, Marc; Gehlen, Christoph
Abstract Epoxy‐coated reinforcement (ECR) as a means of protection against chloride‐induced corrosion of steel in concrete is used in only a few countries due to doubts concerning its effectiveness. A common misconception is that possible defects in the coating are particularly weak points as these might favour high local corrosion rates and thus loss of steel cross‐section. This work discusses why a certain number of small defects can be tolerated. It is argued that prolongation of the initiation phase is caused by a higher critical chloride content compared with uncoated steel due to the "size effect". Additionally, the propagation phase for ECR is likely to be extended due to the severely restricted cathodic area that limits the corrosion rate. This paper presents experimental and numerical tests to verify these assumptions.